Altered gut microbiome in convalescent patients with coronavirus disease 2019 - Lee, Kyoung Hwa; Kim, Yeong Ouk; Dho, So Hee; Yong, Jen J. H.; Oh, Hyun-Seok; Lee, Je Hee; Yang, Seung-Jo; Cha, Inseong; Chun, Jongsik; Lee, Eun Hwa; Jeong, Su Jin; Woo, Wonjin; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionCoronavirus disease 2019 (COVID-19) alters the gut microbiome. This study aimed to assess the association between the disease severity of COVID-19 and changes in stool microbes through a seven-month follow-up of stool collection.MethodsWe conducted a multicentre, prospective longitudinal study of 58 COVID-19 patients and 116 uninfected controls. Differences in the gut microbiota were analysed using 16S ribosomal RNA sequencing. The first stool samples were collected at an early convalescent phase of COVID-19, and the second sample was collected at least seven months after COVID-19 infection.Results and discussionAt the order level, Eubacteriales and Bifidobacteriales decreased, while Bacteroidales and Burkholderiales increased in the COVID-19 group compared to the controls. Alpha diversity also decreased in COVID-19 patients compared to controls, with imperfect recovery of the gut microbiome after seven months. The compositional change in the gut microbiome between the early and late convalescent phases was largest in the moderate and severe groups. The severity of COVID-19 was the most influential clinical variable for microbiome composition (Sum of Sqs = 0.686, P = 0.006), and its effect persisted even after partialling out other effects such as antibiotic use and age. Thus, our study indicates a possible interaction between respiratory viral infection and the composition of the gut microbiota community, warranting future mechanistic and prospective longitudinal studies. Additionally, we were able to detect microbiome changes in patients who were re-infected with SARS-CoV-2. Notably, the dominant bacteria in the re-infected group were Lachnospiraceae and Faecalimonas umbilicata, compared to the one-time infected group.